Mr. Grinan's house.
Image depicts a collapsed building of a Mr. Grinan's house.
Level 1 deterioration.
Item is digitized.
Special Collections Floor.
Keywords: Earthquake 1907. -- Kingston; Kingston. -- Mr. Grinan; Postcards